Modelling, design and analysis of offset, non-orthogonal and profile-shifted face gear drives. (September 2018) - Fu, Xuezhong; Fang, Zongde; Cui, Yanmei; Hou, Xiangying; Li, Jianhua
This article proposes the application of a profile-shifted grinding disc to generate an offset, non-orthogonal and profile-shifted face gear. A detailed investigation of the modelling, tooth geometry and contact characteristics of the offset, non-orthogonal and profile-shifted face gear has been conducted. The mathematical models of the profile-shifted shaper cutter, profile-shifted pinion, profile-shifted grinding disc and offset, non-orthogonal and profile-shifted face gear are established. Considering the topological modification, the tooth surface equation of the offset, non-orthogonal and profile-shifted face gear is deduced. Based on the undercutting and pointing of the tooth surface, the limiting tooth width of the offset, non-orthogonal and profile-shifted face gear is determined, and a mathematical model of tooth contact analysis of the offset, non-orthogonal and profile-shifted face gear drive is established with the alignment errors. Using the approach presented in this article, an example of an offset, non-orthogonal and profile-shifted face gear drive and analytical results are presented.